Children left behind: the effects of temporary labour migration on child care and residence patterns in rural South Africa - Kautzky, Keegan Joseph Michael (My University, 2010)
Background: The rural South African population is characterised by high and stable levels of male temporary migration and rapidly rising levels of female temporary migration, with approximately 60% of men and 20% of women between the ages of 20 and 60 years absent from the home for more than 6 months of the year. Despite the magnitude of this social phenomenon, limited research exists analysing its effect on child care and children’s residence patterns. Objectives: The purpose of this study is to examine temporary labour migration patterns as a household coping strategy in rural northeast South Africa in 2002 and 2007, describe characteristics of the children left behind, and to assess the effect of temporary migration on child care patterns, specifically analysing household variation in child care and residence by sex and refugee status of the migrant. Methods: An analytic cross-sectional study was conducted on approximately 83,000 individuals in 14,000 households in 25 villages of the Agincourt sub-district of the Bushbuckridge region of Limpopo Province. Data was collected in a special module on temporary migration incorporated into the annual Agincourt Health and Demographic Surveillance System census update in 2002 and 2007. Secondary analysis of the data utilised descriptive statistics and Pearson Chi2 tests of association. Results: The proportion of temporary migrants in the population rose between 2002 and 2007 and now constitutes nearly one-fifth of the population. Nearly three-quarters – 13% of the total population – are labour migrants. A slight increase in the proportion of female and Mozambican descent migrants is observed. Today, three-quarters of temporary labour migrants are male and one-quarter female, three-quarters are South African descent and more than one-quarter are Mozambican descent. Temporary labour migrants with children constitute nearly 6% of the total population. Temporary labour migrants overwhelmingly rely on a single care strategy. Complex care arrangements are far less common, constituting the response of only 5% of migrants. Highly complex care arrangements are rare, but do exist. Child care strategies are becoming increasingly complex over time for all migrants. Female migrants and migrants of South African descent are more likely than male and Mozambican descent migrants to rely on complex care arrangements. The overwhelming majority of migrants keep all children in the same household, maintaining relative stability in care and residence, 10% move children with them, 2% move children elsewhere for care and less than 1% move a childcarer into the household while they are away for work. Less stable child care arrangements are increasingly utilised over time. If the migrant is male, children are more likely to remain in the same household; if the migrant is female, children are more likely to move with the migrant. Approximately one-fifth of children in the population are effectively left behind by temporary labour migrants today, a decline from nearly one-third in 2002. There is significant variation in child care, residence and decision-making authority among relatives: mothers and stepmothers provide the majority of care in the absence of a migrant, with grandmothers a secondary and female siblings and aunts a tertiary source of child care.
Thesis (M.P.H.), Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: child care; rural South Africa; temporary child care